From statin efficacy to everyday effectiveness: Studying the gap in between. - Ruokoniemi, Päivi (Annales Universitatis Turkuensis D 1165, 2015)
Statins are indicated for preventing cardiovascular disease events. Patients with diabetes have a risk of major cardiovascular events double the risk of their peers without diabetes. Thus, clinical treatment guidelines recommend statins for the management of diabetic dyslipidemia. The evidence base for statin use in cardiovascular disease derives from the randomized controlled statin trials designed to prove statin efficacy under ideal conditions, among a homogenous study population meeting strict trial eligibility criteria. This thesis was implemented as four pharmacoepidemiological statin studies using register data on realworld statin users. The overall purpose was to evaluate the trends, patterns and effectiveness of statin use in everyday life. More specifically, nationwide secular trends in statin use in Finland were analysed, especially among patient groups which had been underrepresented in the statin trials. Furthermore, the benchmarking statin trials in diabetes, the Heart Protection Study and the Collaborative Atorvastatin Diabetes Study, were evaluated for their representativeness for real-world diabetes care with the emphasis placed on adherence to statin use. The association between good adherence and the incidence of major cardiovascular events in the real-world was further investigated in diabetes. These studies demonstrate that statin initiations increased from 1995 to 2005 in Finland. The increase was most pronounced among those aged at least 75 years and was observed already before the publication of rigorous trial data conducted in elderly subjects. Thus, statins seem to have been initiated in clinical practice also going beyond the strict trial eligibility criteria. Nonetheless, low adherence to statin use among the real-world patients with diabetes was found not only to limit the representativeness of the trials for clinical care but also to attenuate in all likelihood their benefits in the real-world. In fact, good adherence to statin use was found to associate with a decreased risk for major cardiovascular events in patients with diabetes. In conclusion, these studies highlight the importance of good adherence to statin use in clinical practice in order to obtain the full therapeutic value demonstrated in the statin trials. Simply increasing the number of statin users will not alone suffice in sharing our common resources appropriately.

Statiinien teho ja arkielämän vaikuttavuus: Tutkimus raja-alueesta niiden välissä. Statiinien käyttöaihe on sydän- ja verisuonisairaustapahtumien esto. Diabetespotilailla on kaksinkertainen riski saada merkittävä sydän- tai verisuonisairaustapahtuma diabetesta sairastamattomiin verrattuna. Siksi hoitosuositukset suosittavat statiineja diabeettisen dyslipidemian hoitoon. Statiinien käyttöä sydän- ja verisuonisairaustapahtumien estossa tukeva tutkimusnäyttö perustuu satunnaistettuihin, kontrolloituihin hoitotutkimuksiin, jotka on suunniteltu osoittamaan statiinien teho optimaalisissa olosuhteissa, homogeenisen, tiukat sisäänottokriteerit täyttävän tutkimuspopulaation joukossa. Tämä väitöskirja sisältää neljä lääkeepidemiologista tutkimusta, joissa käytettiin rekisteritietoja arkielämän statiinikäyttäjistä. Tutkimuksen tavoitteena oli tutkia statiinien käytön trendejä, tapoja ja vaikuttavuutta arkielämässä. Statiinien käytössä tapahtuneita ajallisia muutoksia Suomessa analysoitiin erityisesti niissä potilasryhmissä, jotka olivat aliedustettuina statiinihoitotutkimuksissa. Lisäksi merkittävien statiinihoitotutkimusten (Heart Protection Study ja Collaborative Atorvastatin Diabetes Study) edustavuutta arvioitiin käytännön diabeteshoidon kannalta kiinnittämällä erityistä huomiota statiinihoitoon sitoutumiseen. Ohella tutkittiin hyvän statiinihoitoon sitoutumisen ja merkittävien sydän- ja verisuonisairaustapahtumien ilmaantumisen välistä yhteyttä arkielämän diabetespotilailla. Väitöskirjatutkimus osoittaa, että statiinihoitojen aloitukset Suomessa lisääntyivät vuodesta 1995 vuoteen 2005, mikä havaittiin erityisesti 75-vuotiaiden ja sitä iäkkäämpien keskuudessa jo ennen heitä koskevan tutkimusnäytön julkaisemista. Vaikuttaakin siltä, että statiinihoitoja aloitetaan arkielämässä statiinihoitotutkimusten tiukkojen sisäänottokriteereiden sanelematta. Väitöskirjatutkimus kuitenkin osoitti, että arkielämän diabetespotilaiden heikompi statiinihoitoon sitoutuminen ei pelkästään rajoittanut arvioitujen hoitotutkimusten edustavuutta, vaan todennäköisesti myös laimentaa statiinihoidosta saatavaa hyötyä. Väitöskirjatyössä nimittäin havaittiin, että diabetespotilailla hyvään statiinihoitoon sitoutumiseen liittyy pienempi sydän- ja verisuonisairaustapahtumien riski. Yhteenvetona todetaan, että tämä väitöskirjatyö osoittaa hyvän statiinihoitoon sitoutumisen merkityksen tavoiteltaessa kliinisissä tutkimuksissa osoitettua statiinien hoidollista arvoa arkielämässä. Statiinien käyttäjämäärien kasvattaminen ei yksinään riitä kohdennettaessa yhteisiä voimavarojamme asianmukaisesti.